The Art of Bosch - A Mirror to Death and Beyond - Oliveira, Abílio; Araújo, Gabriela; Rodrigues, Rute (Mediterranean Journal of Social Sciences, 2012)
Who really pays attention to poetry, philosophy, painting or other art form? We rather seek for what is immediately needed orquickly consumable, what doesn't bother nor disturb us. Emotions and cultural products are strongly linked. But the perception of artdepends on how it impresses us. Art can confront us with a reality. In a civilization dominated by images, through the media, advertisingand virtual worlds, art, like life and death, is rarely valued. We approached on this study, the way in which college students - of bothsexes, from courses of management, history and psychology - interpreted the image/painting ‘Paradise: Ascent of the Blessed’, fromHieronymus Bosch, which alludes to death and beyond-death. We analyzed the thoughts, feelings, images and symbols that emergedfrom their answers, through open questions, after seeing the image/painting. Men revealed security, like they were watching forsomething they see as controllable and far away from them. Women expressed an active emotional involvement, as well as fear, beliefin God and hope in finding a path through the darkness, revealing an intense feeling of proximity before death and immortality. Studentsof psychology, in particular, revealed a more emotional reaction to the image/death, than the future historians. The conceptions of thefirst ones are closer to the women's perspectives, while the others resemble those of men. This work invited us to reflect aboutourselves, the power of images, death, and on what lies beyond death and life.